Rekonstruksi Pendidikan Keluarga Pada Masa Pandemi (Studi Pada Walimurid SMPI Al Hasanah Kota Bengkulu) - Zufikar Zulfikar (Al-Bahtsu : Jurnal Penelitian Pendidikan Islam, 2022)
This thesis studied the reconstruction of family education during the covid-19 pandemic. The purpose of this study was to determine the family's readiness in facing the pandemic covid-19, teaching material provided, the learning methods applied by the teacher, and the obstacles faced by parents and teachers. This type of research was descriptive qualitative. The method of determining the sample used purposive sampling technique. Data collections were interviews and documentation. The data source in this study is divided into two, namely primary data and secondary data. The primary data in this study were parents and teachers. Whereas the secondary data were the principal and the administration. Staff the results of this study were (1) family readiness in the face of a pandemic. Transferring the child's learning process to took home certainly requires greater cooperation from parents. Therefore, it took the readiness of parents in controlling themselves before starting to teach children during the learning process from home. Parents must be able to control themselves over what they are going through and guide their children calmly and patiently. (2) Teaching materials provided during the pandemic. During this pandemic, teaching material are given to students namely moral education, aqeedah, and worship (3) Methods of learning is applied during the pandemic. Online online learning was part of special offers in the era of the corona virus pandemic., (4) Constraints was faced by parents and teachers. Decreasing child's enthusiasm of learning. This was due to quite a lot of tasks, mis understanding of the tasks given. The emergence of a sense of saturation because they have to adjust the material or learning design that has been previously prepared.